Providing Legal Assistance For Defendants In Examination Of Criminal Cases In State Courts - Hadi Purnomo (Dalihan Na Tolu: Jurnal Hukum, Politik dan Komunikasi Indonesia, 2023)
Legal assistance is carried out through the courts. One of the providers of assistance is the Legal Aid Institute, which is a legal aid program provided in order to lighten the burden and is also useful for creating justice and legal protection for the general public. The problem in this research is how to provide legal assistance in criminal cases and the factors that inhibit the implementation of providing legal assistance to defendants in criminal cases. This research is a descriptive-analytical type of research. The method used here is a normative juridical approach. Data collection techniques were carried out using general literature study research, reviewing regulations, journals, textbooks and articles and field studies via the internet by opening sites or websites available on the internet. Data obtained from the research system is collected based on problems and then carried out qualitative analysis, namely carrying out an analysis of laws and regulations relating to Legal Protection. Based on the results of research regarding the analysis of the implementation of providing legal assistance to defendants in criminal cases, the implementation of providing legal assistance can be done through the courts, and the Legal Aid Institute and can also be done with the direct initiative of an advocate who volunteers to accompany him. Factors delaying the provision of legal aid to defendants in criminal cases include; law enforcement factors, community factors, cultural factors, infrastructure and facilities factors.